2021
DOI: 10.1111/pai.13445
|View full text |Cite
|
Sign up to set email alerts
|

Medical clown support is associated with better quality of life of children with food allergy starting oral immunotherapy

Abstract: Background The start of oral immunotherapy (OIT) for food allergy is a critical period in the treatment process, with a potential to influence patient quality of life (QOL) and subsequently treatment outcome. The association of medical clowning with QOL at OIT initiation was examined. Methods Children aged 4‐12 years supported by a medical clown (MC) during the induction week of OIT for food allergy were studied. Children in the same age range starting OIT without the support of a MC served as controls. Parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 30 publications
2
15
1
Order By: Relevance
“…Only 2 studies [15,23] that reported significant interventions on quality of life did not show a high or serious level of risk.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 2 studies [15,23] that reported significant interventions on quality of life did not show a high or serious level of risk.…”
Section: Resultsmentioning
confidence: 99%
“…The interventions provided were consultants, [19,21] providing educational materials, [15,20] cognitive behavioral therapy, [22] practice, [16,17] support, [23] and peer mentoring. [18] Among them, providing educational materials [15] and support [23] were reported as effective interventions for the children and parents' quality of life (Table 2).…”
Section: Interventionmentioning
confidence: 99%
See 3 more Smart Citations